Neuroprotective effect of sacha inchi oil (Plukenetia volubilis L.) in an experimental model of epilepsy - Herrera-Calderon, O. (2019)
Background: Experimental studies have demonstrated that fatty acids such as omega 3 and 6 have anti-inflammatory, anticonvulsant, cardio protective and anti-tumor effects. Objective: The main objective was to determine the protective effect of sacha inchi oil on pentylenetetrazoleinduced seizures in albino mice. Material and Methods: Thirty male Balb/C albino mice of 8 weeks of age were purchased from the National Institute of Health (Lima-Peru). The animals were divided into 5 groups of 6 animals each one. Group I: Control; PTZ (pentylenetetrazole 80 mg / kg, s.c.). II: PTZ + Diazepam (1 mg / kg; s.c.). Group III, IV, V: PTZ + sacha inchi oil at single doses of 250, 500, 1000 mg / kg respectively orally. Sacha inchi oil was administered 30 minutes before induction of seizures by PTZ. Next, various parameters such as latency, seizure frequency, duration and score were scored according to Racine scale. The program Graph Pad Prism v.4 was used for statistical analysis. Results: As result, the experimental group treated with sacha inchi oil at maximum dose of 1000 mg/kg showed better results in response to PTZ induced seizure; low levels of seizures, frequency and duration (P<0.001; ANOVA, P <0.001 Post-hoc Dunnett test). Conclusion: It is concluded that Sacha inchi oil presented anticonvulsant effect at the highest doses tested being very similar to Diazepam. The main mechanism could be by reducing free radical and improving GABA levels in the brain.